New Union Organizing: A Test of the Ashenfelter-Pencavel Model of Trade Union Growth - Adams, Arvil V.; Krislov, Joseph (Quarterly Journal of Economics, 1974)
Introduction and summary, 304. — The Ashenfelter-Pencavel model, 305. — Testing the Ashenfelter-Pencavel model, 307.